DEVELOPING AN E-MODULE OF LOCAL HISTORY ON RELIGIOUS TOLERANCE IN TULUNGREJO VILLAGE WITH ADDIE MODEL: DEVELOPING AN E-MODULE OF LOCAL HISTORY ON RELIGIOUS TOLERANCE IN TULUNGREJO VILLAGE WITH ADDIE MODEL - Ninik Anggraeini; Nurul Umamah; Sumardi Sumardi (JURNAL HISTORICA, 2019)
The 2013 curriculum is designed to strengthen the character of students and national identity.The objectives of the history subject are developing national values, forming awareness andengaging local events in a series of Indonesian histories. Learning history by utilizing localhistory is important to embrace local wisdom values (local genius). Based on the needs analysisperformed in 3 high schools in Banyuwangi, it can be seen that 60.71% used textbooks and asmany as 83.33% of students still do not recognize about the local history around theirsurroundings. This study aims to produce effective e-module of local history learning for historylearning. Development model engaged ADDIE model. The instruments used werequestionnaires, interviews, observations, tests, and documentation. The results showed that (1)the e-module of local history used in history learning obtained results from material expertvalidation is 77.64% means â€œgoodâ€ qualifications, language validation is 92% means â€œverygoodâ€ qualifications , and learning design expert validation is 90% means â€œvery goodâ€qualifications. The results of individual trials conducted on educators showed the percentage of82.22% means â€œgoodâ€ qualifications. The results of the small group trials show the results ofn-gain 68.93 with a moderate level of effectiveness. The results of field trials show the resultsof the calculation of n-gain 75.56 with a high level of effectiveness. Based on the results of thestudy, e-module of local history learning effectively used as learning resources for students.Keywords: Electronic Modules, Local History, ADDIE, Effectiveness